IMMERSED BOUNDARY METHODS - Mittal, Rajat; Iaccarino, Gianluca (Annual review of fluid mechanics, 2005)
The term 'immersed boundary method' was first used in reference to a method developed by Peskin (1972) to simulate cardiac mechanics and associated blood flow. The distinguishing feature of this method was that the entire simulation was carried out on a Cartesian grid, which did not conform to the geometry of the heart, and a novel procedure was formulated for imposing the effect of the immersed boundary (TB) on the flow.